Estrogen exacerbates mammary involution through neutrophil-dependent and -independent mechanism - Lim, Chew Leng (2020)
There is strong evidence that the pro-inflammatory microenvironment during post-partum mammary involution promotes parity-associated breast cancer. Estrogen exposure during mammary involution drives tumor growth through neutrophils' activity. However, how estrogen and neutrophils influence mammary involution are unknown. Combined analysis of transcriptomic, protein, and immunohistochemical data in BALB/c mice showed that estrogen promotes involution by exacerbating inflammation, cell death and adipocytes repopulation. Remarkably, 88% of estrogen-regulated genes in mammary tissue were mediated through neutrophils, which were recruited through estrogen-induced CXCR2 signalling in an autocrine fashion. While neutrophils mediate estrogen-induced inflammation and adipocytes repopulation, estrogen-induced mammary cell death was via lysosome-mediated programmed cell death through upregulation of cathepsin B, Tnf and Bid in a neutrophil-independent manner. Notably, these multifaceted effects of estrogen are mostly mediated by ERα and unique to the phase of mammary involution. These findings are important for the development of intervention strategies for parity-associated breast cancer.